“We're not worth it”: Canadian parole officers' self-worth contingencies — a valuation for job fitness? - Micheal P. Taylor; Rosemary Ricciardelli (Social Sciences and Humanities Open)
In this article, we explore the social environment of Canadian federal parole officers (POs) through a study on seven self-worth contingencies (i.e., recognition, images, comparisons, ideology, kinship, competence, and virtue) adopted for public safety contexts. We qualitatively investigate 28 POs' perceptions, taking a semi-grounded constructivist approach to interview data, and learn how parole officers experience esteem at work. We demonstrate how participants come to recognize themselves through comparisons with other public safety roles, and we situate our findings within the broader literature on probation/parole officer mental health. Using self-determination and introjection theory as our conceptual framework, we identify a paradox. We observe that POs who seek esteem by comparing themselves to others and use techniques to project self-worth likely experience greater distress. In contrast, we surmise those whose self-worth is rooted in authenticity, reflected through abstracted self-construal and an internalized locus of controlexperience greater well-being. Limitations to our study's findings and the implications for future research are offered while theorizing how human resources may be improved in correctional work.